Key Inflammatory Processes in Human NASH Are Reflected in Ldlr−/−.Leiden Mice: A Translational Gene Profiling Study - Morrison, Martine C.; Kleemann, Robert; van Koppen, Arianne; Hanemaaijer, Roeland; Verschuren, Lars (Frontiers in Physiology, 2018)
Introduction: It is generally accepted that metabolic inflammation in the liver is an important driver of disease progression in NASH and associated matrix remodeling/fibrosis. However, the exact molecular inflammatory mechanisms are poorly defined in human studies. Investigation of key pathogenic mechanisms requires the use of pre-clinical models, for instance for time-resolved studies. Such models must reflect molecular disease processes of importance in patients. Herein we characterized inflammation in NASH patients on the molecular level by transcriptomics and investigated whether key human disease pathways can be recapitulated experimentally in Ldlr−/−.Leiden mice, an established pre-clinical model of NASH. Methods: Human molecular inflammatory processes were defined using a publicly available NASH gene expression profiling dataset (GSE48452) allowing the comparison of biopsy-confirmed NASH patients with normal controls. Gene profiling data from high-fat diet (HFD)-fed Ldlr−/−.Leiden mice (GSE109345) were used for assessment of the translational value of these mice. Results: In human NASH livers, we observed regulation of 65 canonical pathways of which the majority was involved in inflammation (32%), lipid metabolism (16%), and extracellular matrix/remodeling (12%). A similar distribution of pathways across these categories, inflammation (36%), lipid metabolism (24%) and extracellular matrix/remodeling (8%) was observed in HFD-fed Ldlr−/−.Leiden mice. Detailed evaluation of these pathways revealed that a substantial proportion (11 out of 13) of human NASH inflammatory pathways was recapitulated in Ldlr−/−.Leiden mice. Furthermore, the activation state of identified master regulators of inflammation (i.e., specific transcription factors, cytokines, and growth factors) in human NASH was largely reflected in Ldlr−/−.Leiden mice, further substantiating its translational value. Conclusion: Human NASH is characterized by upregulation of specific inflammatory processes (e.g., “Fcγ Receptor-mediated Phagocytosis in Macrophages and Monocytes,” “PI3K signaling in B Lymphocytes”) and master regulators (e.g., TNF, CSF2, TGFB1). The majority of these processes and regulators are modulated in the same direction in Ldlr−/−.Leiden mice fed HFD with a human-like macronutrient composition, thus demonstrating that specific experimental conditions recapitulate human disease on the molecular level of disease pathways and upstream/master regulators.